Polymeric microspheres: a delivery system for osteogenic differentiation. (19th June 2017) - Patel, Rajkumar; Patel, Madhumita; Kwak, Jeonghun; Iyer, Arun K.; Karpoormath, Rajshekhar; Desai, Shrojal; Rarh, Vimal
Abstract : Advanced drug delivery systems employing controlled release technology are being developed to address many of the difficulties associated with traditional methods of drug administration. Controlled release technology involves the use of devices such as polymer‐based disks, rods, pellets, or microspheres (MSs) that encapsulate drugs, genes, cytokines, and growth factors and release them in specific location within the body in a controlled fashion, for relatively long periods of time. Among these, microencapsulation is one of the core technologies used in polymer‐based drug delivery systems. In this regard, MS serves as microcarriers for sustain drug release facilitating their use for invasive or minimally invasive treatment. MS has significant potential for the application in bone repair, intra‐articular treatment of osteoarthritis, and biological bone growth. The present review compiles the recent advances in polymeric MS for application in bone and cartilage regeneration. Copyright © 2017 John Wiley & Sons, Ltd.